2003
DOI: 10.1002/etc.5620220205
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of metals to membrane filters in view of their speciation in nutrient solution

Abstract: Filtration of a solution may lower metal concentrations through adsorption of metal species to the filter. Processes such as filter-sterilizing nutrient solution and filtration of field water are sensitive to these sorption artifacts, yet basic data on the affinity of different filters for metals are lacking. This article describes the adsorption of five metals to eight types of 0.2-microm membrane filters used for sterilizing a plant (Lemna minor L.) culture medium. Filters of cellulose acetate, cellulose nit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 26 publications
0
34
0
Order By: Relevance
“…The dialysis bags were completely submerged and kept in the dark under aerobic conditions in a thermo-stated water bath at 25°C. We chose cellulosic dialysis bags because they exhibit minimal adsorption affinity for di-and tri-valent metallic cations at the pH range considered in our experiments (Farrah and Pickering, 1978;Weltje et al, 2003).…”
Section: Solubility Measurementsmentioning
confidence: 99%
“…The dialysis bags were completely submerged and kept in the dark under aerobic conditions in a thermo-stated water bath at 25°C. We chose cellulosic dialysis bags because they exhibit minimal adsorption affinity for di-and tri-valent metallic cations at the pH range considered in our experiments (Farrah and Pickering, 1978;Weltje et al, 2003).…”
Section: Solubility Measurementsmentioning
confidence: 99%
“…Microfiltration (MF) using 0.45 m cut-off filter membranes is commonly utilized to determine the dissolved metal fraction in e.g., surface waters or soil solutions [7,16], while 0.2 m filtration is routinely used for sterilization of for instance nutrient media [38]. However, solely based on size, nanoparticles should be allowed to permeate during MF due to their extremely small dimensions, thereby ending up in the so-called "dissolved" fraction.…”
Section: Introductionmentioning
confidence: 99%
“…The membrane-fouling phenomena and other filtration induced artefacts occurring during trace metal analysis have been investigated [13,38,29,16].…”
Section: Introductionmentioning
confidence: 99%
“…They also found that the loss of trace metals (lead and copper, among others) was especially significant after filtering with a 0.45-μm nylon syringe filter. Weltje et al (2003) examined sorption of various metals in nutrient solution onto an array of 0.22-μm membrane filters, including those made of cellulose acetate, cellulose nitrate, mixed cellulose ester, nylon, p o l y a m i d e , p o l y c a r b o n a t e , p o l y e s t e r, a n d polyvinylidene. Using a filter holder, a syringe was used to push the samples through.…”
Section: Introductionmentioning
confidence: 99%